2015
DOI: 10.1111/joor.12376
|View full text |Cite
|
Sign up to set email alerts
|

Oral appliance treatment in moderate and severe obstructive sleep apnoea patients non‐adherent to CPAP

Abstract: SummaryThe aim of this retrospective study was to evaluate the effect of individually adjusted custom‐made mandibular advancement device/oral appliance (OA) in treatment of patients with moderate and severe obstructive sleep apnoea (OSA), who were non‐adherent to continuous positive airway pressure (CPAP) therapy. During 2007‐2013, 116 patients with moderate (n = 82) and severe (n = 34) OSA non‐adherent to CPAP treatment were referred for dental management with an individually adjusted OA at a specialist sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 30 publications
3
47
1
Order By: Relevance
“…[7,8] Mandibular advancement devices (MADs) are the most common class of oral appliances used to treat snoring or OSA and are considered simple, safe, and cost-effective options. [9,10] All devices protrude the mandible and induce changes in the anterior position of the tongue, soft palate, and lateral pharyngeal wall, resulting in improved airway patency. [11,12] Recent evidence has suggested that MADs also improve sleep-disordered breathing and are also typically used for OSA patients who demonstrate retroglossal area narrowing with mild OSA symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] Mandibular advancement devices (MADs) are the most common class of oral appliances used to treat snoring or OSA and are considered simple, safe, and cost-effective options. [9,10] All devices protrude the mandible and induce changes in the anterior position of the tongue, soft palate, and lateral pharyngeal wall, resulting in improved airway patency. [11,12] Recent evidence has suggested that MADs also improve sleep-disordered breathing and are also typically used for OSA patients who demonstrate retroglossal area narrowing with mild OSA symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MADs may be suggested to patients who have difficulty in tolerating CPAP treatment or are unable to undergo sleep surgery as an alternative treatment modality. [9] MADs are classified according to adjustability when they contain a mechanism to increase the degree of mandibular advancement, or fixed when they are manufactured in a fixed position. They can be designed to monobloc or duobloc, depending on whether the MAD is composed of 1 or 2 pieces.…”
Section: Introductionmentioning
confidence: 99%
“…The duration from appliance prescription to followup polysomnography in the STOP group was longer than that in the control group (147 [115-215] vs 113 [70-198] days, P < .05, Mann-Whitney U test). The apnea-hypopnea index (AHI) was improved in both the STOP group (16 [10][11][12][13][14][15][16][17][18][19][20][21][22] to 3 [2][3][4][5][6][7] events/h, P < .05) and the control group (18 [13][14][15][16][17][18][19][20][21][22][23][24][25][26] to 6 [3][4][5][6][7][8][9][10][11] events/h, P < .05). However, a greater percentage of subjects achieved a follow-up AHI of < 5 events/h with a > 50% reduction in baseline AHI in the STOP group (44 of 69 patients, 64%) than in the control group (94 of 228 subjects, 41%) (P < .05, chi square test).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated eicacy of oral appliance therapy comparable to CPAP in selected patients [56,57]. While oral appliances help to decrease AHI/RDI/REI across all severity levels, there are few reported factors that consistently predict improvement in OSA using oral appliances.…”
Section: Update On Oral Appliance Therapymentioning
confidence: 99%
“…Among these are changes in pharyngeal geometry under drug-induced sleep endoscopy (DISE) [58] and nasoendoscopy to assess velopharynx/oro/hypopharyngeal geometry [59]. In the study of Gjerde [57], low oxygen levels carried a high predictive value for failure with oral appliance therapy.…”
Section: Update On Oral Appliance Therapymentioning
confidence: 99%